Rare Distal Anterior Choroidal Artery Aneurysm - Muhammad Zafrullah Arifin; Julius July; Bilzardy Ferry; Ahmad Faried (International Journal of Integrated Health Sciences, 2016)
Objective: To describe a rare patient with ruptur aneurysm case of distal anterior choroidal artery (AChA) and intraventricular hemorrhage. A 56-year old female came to our hospital with chief complaint sudden onset of severe headache and vomiting.Methods: Head computed tomography (CT)-scan and angiography on the lesion was performed at the Department of Radiology, Siloam Hospital, Tangerang, Indonesia.Results: Head CT-scan imaging revealed an intraventricular hemorrhage, primarily in the right lateral ventricle, with slight enlargement of both lateral, 3rd and 4th ventricles. Angiography examination revealed a round vascular lesion at the wall of the posterior cornu of the lateral ventricle and an occlusion of the M1 base segment of the left middle cerebral artery.Conclusions: The lesion, distal AChA aneurysm, at the posterior cornu was reached using an infratemporal lobe approach with the help of neuronavigation. Microsurgical clipping was successfully performed.Keywords: Aneurysm, distal anterior choroidal artery, neuronavigation DOI: 10.15850/ijihs.v4n2.837